THE THERAPEUTIC POTENTIAL OF TEN SACRED PLANTS (DASHAPUSHPA) OF KERALA STATE OF SOUTHERN INDIA - ARUN RAJ GR; SHAILAJA U; RAO PRASANNA N and AJAYAN S
Kerala state is famous for its medicinal plant wealth and the tradition of indigenous system of therapy, specifically the Ayurveda. Dashapushpam constitute a group of ten potential herbs which are culturally and medicinally significant to the people of Kerala state. They are a group of ten herbs with which the ladies decorate their hairs and dance the thiruvathira kali on the day of thiruvathira in the Malayalam month of dhanu (December to January). Dashapushpas are also been eaten in the form of karkkadaka kanji in karkkidaka masam (during mid-July to mid August) to get better health in the upcoming monsoon season. Also these plants are used in folklore practice in lithiasis, gonorrhea, vomiting, indigestion, skin diseases, intermittent fever, flatulence, urogenital diseases etc. Most of them are scientifically validated for various bioactivities. Still there are lots of possibilities for potential pharmacological activities from these herbs, yet to be explored. This article would throw light on the therapeutic potential of these ten sacred plants aiding to further propagation of these plants.